Best interest of children in the division of family business as matrimonial property: the civil and shariah courts’ perspectives in Malaysia - Abd Ghadas, Zuhairah Ariff; Ibrahim, Norliah (LexisNexis, 2011)
A family business is an interesting business structure as it connotes a structure in which the interests in ownership, management and business overlap upon one another. There is also a confinement of ownerships on family members to ensure business legacy of the family name. This confinement would be prejudiced in the case of divorce as the family structure shall be affected or broken by separation of the parent. In many cases, interest in the business shall be divided between the spouses according to their interest or contribution to the business. The case law shows that, the issue of the best interest of the child is seldom applied in determination and division of interest/shares in business as a matrimonial property; albeit the family business structure was initially meant for the children and for the continuation of the family name. This issue might be resolved if the courts take into consideration the element of participation in business rather than the quantum of interest in the business in determining and dividing the matrimonial property. The participation right ensures the continuity of the family ownership in the business despite the fact that a divorce has taken place between the parents; such right could be delegated or transferred by the divorced parties to the children in due course or in the future. This approach would ensure that the continuity of the business achieved the initial/main purpose of its establishment and would bestow long term benefits to the children.